Analisis Kadar Rasio Neutrofil Limfosit (RNL) pada Balita dengan Pneumonia di Rsia Ananda Kota Makassar - Nur Azizah; Henny Fauziah; Saharuddin; Saraswati W. Hartono; Ambo Asse (Universitas Islam Negeri Alauddin Makassar, 2024)
The neutrophil-to-lymphocyte ratio (NLR), as a predictor of inflammation obtained from the results between absolute neutrophils and absolute lymphocytes, shows an increased level in various diseases that trigger inflammation, especially in pneumonia with complications and a higher mortality rate. This study aimed to analyze NLR levels in children (aged 12-59 months) with pneumonia and non-pneumonia (upper respiratory tract infection/URTI) at Ananda’s Mother and Child Hospital in Makassar City. This study used an observational analytic study with a cross-sectional approach. The study sample consisted of 139 samples from children (aged 12-59 months), divided into pneumonia and non-pneumonia (URTI) samples. These samples had routine blood test results and complete medical record data. Data analysis used univariate and bivariate tests (Independent T Test). In this study, the average NLR in pneumonia samples was lower than non-pneumonia (URTI), and there was also no significant difference between NLR levels in pneumonia and non-pneumonia (URTI). Therefore, this study's conclusion shows no significant increase in NLR levels of children (aged 12-59 months) with pneumonia.